PROSES MANUFAKTUR ALAT PRESS BRIKET DENGAN KAPASITAS 15 KG/JAM - KHOLID IRFAN FIRMANSYAH (2021)
Briquettes are one of the alternative energy derived from biomass as a substitute for petroleum. Raw materials for making briquettes can be found in daily life, one example is wood grain waste. In the manufacture of press tools that are still fairly expensive tools that inhibit the use of briquettes. In this writing, the author raised the theme of "briquette press tool manufacturing process". The purpose of this research is the production of briquette presses with manufacturing processes that do not spend too much production costs and save production time and choose the right material. The manufacturing process is chosen by analyzing the process using the parameters of the length of time worked, the costs used in the manufacture of tools and the purchase of the required parts, as well as the selection of materials to be used in the manufacture of briquette presses. The results of this study produced a briquette press with a capacity of 15.48 kg / hour or 363 briquettes / hour with a total cost spent of Rp.1.193.096.96 and the total time in the manufacture of the tool is 4.54 hours.